Effect of Integrated Nutrient Application on Growth and Yield of Maize: Nutrient Application and Maize Yield - Abid, Muhammad; Ahmed, Riaz; Umair, Adnan; Islam, Muhammad (Biological Sciences - PJSIR, 2015)